2018
DOI: 10.1080/10942912.2018.1460757
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds produced by Bacillus species alkaline fermentation of bambara groundnut (Vigna subterranean (L.) Verdc) into a dawadawa-type African food condiment using headspace solid-phase microextraction and GC × GC–TOFMS

Abstract: Volatile compounds produced by Bacillus species alkaline fermentation of bambara groundnut (Vignasubterranean (L.) Verdc) into a dawadawa-type African food condiment using headspace solid-phase microextraction and GC × GC-TOFMS, The reports on the volatile compounds of a dawadawa-type African food condiment produced from the alkaline fermentation of bambara groundnut (Vigna subterranea (L.) Verdc.) using Bacillus starter cultures are limited. Volatile compounds were isolated from dawadawa-type condiments using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…It was observed that in dl-7-azatryptophan, the peak area of UHD (1.22%) was higher than that of DD (0.28%), while UHD has the highest percentage peak area in all the vitamins reported. Furans are heterocyclic compounds, known to possess sweet, roasted, burnt, caramel and sugar notes as previously reported in dawadawa ( Akanni et al., 2018a ; Azokpota et al., 2008 ).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…It was observed that in dl-7-azatryptophan, the peak area of UHD (1.22%) was higher than that of DD (0.28%), while UHD has the highest percentage peak area in all the vitamins reported. Furans are heterocyclic compounds, known to possess sweet, roasted, burnt, caramel and sugar notes as previously reported in dawadawa ( Akanni et al., 2018a ; Azokpota et al., 2008 ).…”
Section: Resultsmentioning
confidence: 75%
“…Esters were the principal compounds reported in this study. Other similar studies on fermented condiments contradict this observation, with pyrazines being the major constituent in sonru , afitin , iru ( Azokpota et al., 2008 ), acids the dominant group in castor oil bean fermented condiment ( Ojinnaka and Ojimelukwe, 2013 ), aldehydes in locust bean daddawa , soybean and melon seed ogiri ( Onyenekwe et al., 2012 ), while aldehydes, acids and ketones were reported to dominate dawadawa from BGN using Bacillus species ( Akanni et al., 2018a ). Nevertheless, esters are major metabolite groups common to several fermented condiments in Africa and are mostly formed during fermentation by esterification of alcohols with fatty acids ( Fan and Qian, 2005 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In this context, it had not only excellent resolution for all compounds but also maintained desirable sensitivity. Two columns of different polar stationary phases are connected in series to perform orthogonal separation (Akanni et al, 2018;Shellie et al, 2001). A first-dimensional column separates the detected sample components, focused by a modulator, and then pulsed into a second-dimensional column for a second separation operation (Adahchour & Brinkman, 2008;Setyaningsih et al, 2019).…”
Section: Introductionmentioning
confidence: 99%